A Case Report of COVID-19 and Subacute Thyroiditis in Fars, Iran - Zahra Montaseri; Jalal Karimi; Ali Ghanbariasad; Babak Pezeshki; Hossein Kargar (Fasa University of Medical Sciences, 2023)
Background & Objective: COVID-19 can affect thyroid gland and causes subacute thyroiditis. Case Presentation: We introduced a 60-year-old woman with an initial symptom of anterior cervical pain without any other constitutional symptoms. Nasopharyngeal and oropharyngeal swabs were detected positive for COVID-19 using RT-PCR assay. According to ultrasonographic,  laboratory (lowered TSH, elevated CRP and ESR), and physical findings, subacute thyroiditis was found following the SARS-CoV-2 infection. Conclusion: As subacute thyroiditis associated with SARS-Cov-2 may be represented without any fever, ruling out this infection in these patients is considerable.